Protective Effect of Lemon Essential Oil and Its Major Active Component, D-Limonene, on Intestinal Injury and Inflammation of E. coli-Challenged Mice - Zhao, Chen; Zhang, Zhuo; Nie, Dechao; Li, Yanling (Frontiers in Nutrition, 2022)
Inflammatory diseases are a major threat to public health. Natural plant essential oils (EOs) possess anti-inflammatory and anti-oxidative activities. The objective of this study was to investigate the anti-inflammatory effect and mode of action of lemon essential oil (LEO), and its main active component, d-limonene, with different doses on intestinal inflammation of mice. Sixty-four 5-week-old male balb/c mice weighing 22.0 ± 1.5 g were randomly assigned into one of 8 treatments (n = 8/treatment), including normal saline group (NS), Escherichia coli (E. coli) group, and either LEO and d-limonene essential oil (DEO) group supplemented at 300, 600, and 1,200 mg/kg of BW, respectively. After the pre-feeding period, the mice were fasted for 12 h, the mice in the NS group and the E. coli group were gavaged with normal saline, and the mice in the LEO group and DEO group were gavaged with respective dose of EOs for 1 week. One hour after the end of gavage on the 7th day, except that the mice in the normal saline group were intraperitoneally injected with normal saline, the mice in the other groups were intraperitoneally injected with the same concentration of E. coli (108 cfu/ml, 0.15 ml per mouse). The antioxidant indexes were measured including superoxide dismutase (SOD), malondialdehyde (MDA), and myeloperoxidase (MPO) in plasma obtained by taking blood from mouse eyeballs. The inflammatory indexes were measured including interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor alpha (TNF-α) in plasma. The tight junction protein indicators were tested include zona occludens 1 protein (ZO-1), occludin and claudin in mouse duodenum. We found that all of the above indexes for E. coli group were different (P< 0.05) with the NS group. The interaction of EO and dose (E × D) were significant (P < 0.01) for all of the indexes. In addition, LEO at 300 mg/kg BW and DEO at 600 mg/kg BW had better antioxidant and anti-inflammation activity on the infected mice, which reduced (P < 0.05) the plasma concentrations of MDA, MPO, TNF-α, IL-1β, and IL-6, but increased (P < 0.01) the concentrations of SOD. Hematoxylin-eosin (H&E) staining of duodenum observation showed that LEO and DEO reduced inflammatory cell infiltration and maintain the orderly arrangement of epithelial cells. Moreover, supplementation of LEO at 600 mg/kg and DEO at 300 mg/kg BW alleviated (P < 0.05) intestinal barrier injury for increasing the relative expression of ZO-1, occludin and claudin mRNA in mice duodenum. These results showed that the pre-treatment with LEO and DEO had protection of intestinal tissue and inflammation in E. coli infected mice. Both LEO and DEO exhibited activity of antioxidant, anti-inflammatory and alleviating intestinal injury, whereas, compared with DEO, LEO can be active at a lower dosage. Furthermore, as the main active component of LEO, the d-limonene appeared to play not only the major role, but also the joint action with other active components of LEO.